(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Background India has the largest drug consuming population in the world. Adverse drug reactions (ADR) are commonly encountered in daily practice, many of which are preventable . Objective To evaluate the knowledge, attitude and practice of ADR reporting and Pharmacovigilance concept among healthcare professionals. Materials and Methods It was a cross-sectional, questionnaire based survey conducted by the staff of the Department of Pharmacology at Dr.B.R.Ambedkar Medical College and Hospital, Bangalore in March 2017. 92 doctors participated in this study. Statistical analysis Collected data was analyzed by frequency, percentage and mean using the statistical software SPSS version13.0 Results 98% of respondents were aware of the existence of suspected ADR reporting system in India. 54.6% of respondents were of the opinion that non availability of reporting forms discouraged them from ADR reporting. All respondents were of the opinion that ADR reporting system would benefit patient care. 50( 54.3% )of respondents have never even attended any Continuing Medical Education (CME) programme on ADRs, which shows that there is lack of awareness creating programs stressing on the importance of ADR reporting. Conclusion This study revealed that though majority of the health-care professionals had good knowledge and positive attitude about Pharmacovigilance, the actual practice of ADR reporting was unsatisfactory.